EVALUATING TV SEKOLAH AS AN EVIDENCE-BASED TOOL FOR PAUD HI PROGRAM EVALUATION AND DIGITAL CHILD PORTFOLIOS IN KINDERGARTEN SETTINGS - Rochmawati, Nur Intan; Pudjaningsih, Wiwik; Pratama, Ade; Fyanthusany, Desyanne Dhuanyta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Holistic-Integrative Early Childhood Development (PAUD HI) requires routine, evidence-based evaluation to document learning processes and communicate child development to families, yet many kindergarten settings still rely on fragmented documentation. This study examines whether TV Sekolah can function as an evidence-based tool for PAUD HI evaluation and as a digital child portfolio in a kindergarten cluster in Semarang. We employed a mixed-method exploratory design combining questionnaires and documentation/observation of platform use; participants included parents (n=24) and teachers (n=10). Results indicate that parental conceptual understanding remained limited (41.7% understood TV Sekolah, whereas 58.3% did not), but perceived informational value was high: 75.0% reported being satisfied (including 12.5% very satisfied) and 25.0% reported not being satisfied. Most parents also agreed that TV Sekolah increased their involvement in monitoring children’s activities and progress (83.3% agree). Teachers largely judged TV Sekolah effective as evaluation evidence (80% effective), though some reported integration constraints. In conclusion, TV Sekolah shows practical promise for strengthening PAUD HI evaluation and transparency, but schools should provide teacher training, integrate documentation into daily evaluation workflows, and deliver structured parent orientation to close comprehension gaps.